Implementation of AAA on Hotspot Network using RADIUS Server and MikroTik Router (Case Study: SMK Negeri 1 Tabanan) - Afifah, Hasna; Suarjaya, I Made Agus Dwi; Sasmita, Gusti Made Arya (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2025)
The rapid advancement of technology has made the internet a basic necessity for society, including within educational environments. This study aims to implement an AAA (Authentication, Authorization, Accounting) system on the hotspot network at SMK Negeri 1 Tabanan using a RADIUS Server and MikroTik Router. The system is integrated with a shared DNS service from APJII, which automatically blocks access to harmful or restricted websites when users connect to the school network. Additionally, a dynamic bandwidth feature is implemented, allowing bandwidth to increase or decrease based on the traffic conditions of each user profile. The system was developed using the Network Development Life Cycle (NDLC) method, starting from requirements analysis to performance testing using Apache JMeter. Quality of Service (QoS) testing, based on the TIPHON standard, shows that all user categories (Students, Staff, and Guests) received a “Satisfactory” classification, with average index scores ranging from 3.25 to 3.5. The AAA system has proven effective in implementing access authentication and authorization, recording user activity, and improving the security and efficiency of hotspot network management through web-based monitoring using daloRADIUS.